2021
DOI: 10.3389/fvets.2021.681858
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Energy Level on Performance, Plasma Parameters, and Central AMPK Levels in Stressed Broilers

Abstract: This study aimed to characterize the effects of diets with different energy levels on the growth performance, plasma parameters, and central AMPK signaling pathway in broilers under dexamethasone (DEX)-induced stress. A total of 216 1-day-old male broiler chickens were allocated to groups fed with high (HED), National Research Council-recommended (control), or low (LED) energy diets. At 10 days old, chickens were treated with or without dexamethasone (DEX, 2 mg/kg body weight) for 3 consecutive days. HED incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 86 publications
6
7
0
Order By: Relevance
“…We found that DEX injection increased the levels of blood glucose, TP, and TC and the Ca 2+ /P 5+ ratio, and these indices returned rapidly to physiological levels following DEX withdrawal. This results were in agreement with earlier studies [ 20 ] reporting that DEX-treated chickens showed elevated levels of blood TP, TG and TC [ 25 ] and that Holstein heifers suffering road transportation stress had higher levels of plasma cortisol, nonesterified fatty acids, glucose and a higher Ca 2+ /P 5+ ratio [ 1 ]. Clearly, DEX injection-induced simultaneous hyperglycemia and hyperlipidemia, together with DEX itself, are responsible for the change in the number and function of immune cells.…”
Section: Discussionsupporting
confidence: 93%
“…We found that DEX injection increased the levels of blood glucose, TP, and TC and the Ca 2+ /P 5+ ratio, and these indices returned rapidly to physiological levels following DEX withdrawal. This results were in agreement with earlier studies [ 20 ] reporting that DEX-treated chickens showed elevated levels of blood TP, TG and TC [ 25 ] and that Holstein heifers suffering road transportation stress had higher levels of plasma cortisol, nonesterified fatty acids, glucose and a higher Ca 2+ /P 5+ ratio [ 1 ]. Clearly, DEX injection-induced simultaneous hyperglycemia and hyperlipidemia, together with DEX itself, are responsible for the change in the number and function of immune cells.…”
Section: Discussionsupporting
confidence: 93%
“…The contents of LDL-C and HDL-C in serum of HEP group pigs were the highest, indicating that cholesterol turnover and metabolism in liver were increased. Similar results were also found in broilers with increased dietary energy levels causing elevated serum HDL and LDL levels (Hu et al, 2021). In addition, it was found in this study that the serum ALP level of Tibetan pigs under different feeding patterns was within the normal range (40-160 U/L), but the ALP level in Tibetan pigs fed high energy content diet was significantly higher than that in Tibetan pigs fed regular diet or free-ranging, meaning that the liver metabolic process was significantly enhanced (Siller and Whyte, 2018).…”
Section: House Feeding Can Provide Full Mixed Diet For Tibetan Pigs W...supporting
confidence: 85%
“…With increasing levels of ME in diets without and with GAA addition, the birds reduced their FI. This result was expected, based on the literature, because broilers may adjust their FI in response to their energy needs (Leeson et al 1996;Hu et al, 2021). This is linked to metabolic signalization.…”
Section: Discussionsupporting
confidence: 60%